New Land, Volume 1 Four Years in the Arctic Regions - Sverdrup, Otto Neumann 1854-1930 (Cambridge library collection. Polar Exploration, 1904)
This well-illustrated account of polar exploration was originally published in Norway in 1903, and in this two-volume English translation in 1904. It tells the story of the four years spent by Otto Sverdrup (1854–1930) and his crew in surveying and charting the seas and coastlines of the Arctic. Sverdrup had qualified as a ship's master when he first met Fridtjof Nansen, whose Greenland expedition of 1888 he accompanied. He advised on the construction of Nansen's wooden ship, the Fram, and became its master in 1895. Both with Nansen and under his own leadership, he undertook many expeditions. In June 1898, he took the Fram and a crew including several scientists to Ellesmere Island in the Canadian Arctic, where they overwintered for four years. Volume 1 describes the life and work of the first two years, including extensive trips away from the Fram, both on land and on the ice